Health risk study of trace elements in inhalable particles from Southern Yangtze River Delta Region, China - LONG, Liang-Ping (2021)
Recently, airborne particulate matter from outdoor pollution has been classified as carcinogenic substance to humans based on sufficient evidence of epidemiologicaland toxic investigations. Toxicological studies have implicated trace metals in airborne particles as possible contributors to respiratory and cardiovascular inflammation. The exposure data of heavy metals and related health risks were very limited in China, especially in the Yangtze River Delta (SYRD) region. The aims of this study are to: (1) investigate the spatial and seasonal characteristics and sources of trace elements bounded to PM2.5 in the SYRD region; (2) study the bioaccessibility of trace elements bound to PM2.5 in water and simulated lung fluids; (3) investigate size distributions of trace elements and airway deposition fraction of particles in the respiratory system; and (4) perform health risk assessments for adults and children in the SYRD region with the consideration of bioaccessibilities of elements and deposition fractions. Methods used in the study are listed as follows: (1) PM2.5 samples were collected from four representative sites in Hangzhou (LA -rural site and HZ-urban site) and Ningbo city (UN-suburban site and NQ-urban site) from December 2014 to November 2015. Size-resolved samples were collected during haze and non-haze days at an urban site in Ningbo city (NQ) from November 2013 to May 2014. (2) Elemental concentrations were measured by inductively coupled plasma mass spectrometer (ICP-MS) after microwave digestion with acids mixture or sonicated in water and simulated lung fluids (ALF and Gamble's solution); (3) Source apportionments of trace elements were conducted by the methods of enrichment factors, principal component analysis (PCA) and positive matrix factorization (PMF). (4) Deposition fractions of elements were estimated by a Multiple-Path Particle Dosimetry (MPPD) model. (5) Human health risk assessments were assessed by the United States Environmental Protection Agency (USEPA) model. Research results from the study are: (1) The annual PM2.5 mass concentration of 4 sites ranged from 59.73 to 79.12 μgm-3, which exceeded the latest China PM2.5 Class II air quality standard. PM2.5 pollutions were the highest in winter and lowest in summer. Spatially, western sites (LA and HZ) showed higher concentrations of PM2.5, while eastern sites (UN and NQ) showed lower concentrations. Regional transportation was the main reason for the high PM2.5 levels at LA and HZ. (2) The annual mean concentrations of 17 elements (Na, Mg, Al, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd and Pb) in PM2.5 from 4 site ranged from 0.378±0.199 ngm-3 for Co to 631±407 ngm-3 for K. Cr and As were well above the air quality standard. All elements exhibited spatial variation with the highest levels at HZ and the lowest at LA. Meanwhile, elemental concentrations showed clear seasonal trends, with higher concentrations in winter and lower concentrations in summer. Meanwhile, the annual mean water-soluble concentrations of 12 elements (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd and Pb) in PM2.5 ranged from 0.152±0.073 ngm-3 for Co to 152±94 ngm-3 for Zn; All elements show spatial variation with the highest levels at HZ and the lowest at LA. Soluble concentration of trace elements in winter were 1.17-3.28 folds higher than that of summer. The total concentrations of 17 measure elements in fine particles (Dp < 2.1 μm) during the haze period ranged from 0.51 ngm-3(Co) to 1.53 μgm −3 (K) with a sum of 5.53 μgm−3. However, the chemical composition of elements in fine particles was changed during the non-haze days, with a range of 0.24 ngm-3 (Co) to 1.52 μgm −3 (Ca) with a sum of 3.49 μgm−3. (3) The enrichment factors (EFs) of Na, Mg, Al, K, Ca, Ti, Mn, Fe and Co in PM2.5 samples based on total concentrations were less than or close to 10; In comparison, V, Cr, Ni, Cu, Zn, As, Cd and Pb were enriched in aerosols with EFs higher than 10, suggesting the significant impacts by anthropogenic emissions. Additionaly, the water-soluble fractions of most elements (except Ti and Cr) in PM2.5 showed higher EF values than the total fractions. Five sources including coal combustion (4.1%), industry emissions (16.3%), soil dust (61.3%), heavy oil combustion (3.1%) and traffic emissions (15.2%) were identified for the water-soluble concentrations of 12 elements by PCA analysis and PMF modeling. (4) Regarding the bioaccessibilites of elements in PM2.5, mean bioaccessibilities in water are with the order of Pb (72.0%) > Cd (68.7%) >Mn (63.1%) > Zn (57.6%) > Cu (51.6%) > As (38.5%) > Co (34.4%) > Ni (30.1%) > V (26.8%) > Fe (18.5%) > Cr (10.4%) > Ti (10.0%). In particular, the mean bioaccesibilty in ALF presented a decreasing order as follows: Pb (77.5%) >Mn (77.0%) > Cd (73.1%) > Zn (68.4%) > Cu (61.9%) > As (53.1%) > Co (44.8%) > Ni (44.1%) >V (42.0%) > Cr (36.1%) > Fe (24.7%) > Ti (20.4%). Specifically, the mean bioaccessibilty exhibited a decreasing order of Pb (31.2%) > As (30.3%) > Zn (30.0%) > Cu (29.6%) > Mn (27.3%) > Cd (24.9%) > Co (23.7%) > V (15.0%) > Fe (9.0%) > Ni (8.1%) > Cr (6.9%) > Ti (5.2%) in the Gamble's solution. The results from the MPPD model showed particles in the H region have the highest deposition fraction, followed by the P and TB region. The MPPD modeling results also revealed that the deposition fraction of PM2.5 particles in H region was 0.339 and 0.249 for children and adults, respectively. (5) The integrated non-carcinogenic risks based on the water-soluble concentration of toxic elements in PM2.5 and deposition fraction living in all four sampling sites at the SYRD region are 0.19 (LA) -0.29 (HZ) for adults and 0.088 (LA) - 0.13 (HZ) for children, which were lower than the safe level (=1). However, the integrated carcinogenic risks from three exposure pathways posed by six toxic elements (Cr(VI), Co, Ni, As, Cd and Pb) ranged from 9.61×10-6 to 14.4×10-6 for adults and 9.36×10-6 to 14.0×10-6 for children, which mainly caused by As that emitted from coal combustion. Dermal contact contributed the highest risks, followed by inhalation and ingestion. Among the four sites, HZ had the highest health risks, followed by NQ, UN and LA. Furthermore, health risks assessed with total elemental concentration in fine (Dp < 2.1 μm) and coarse (2.1μm < Dp < 9.0μm) particles. It was found that both non-carcinogenic of adults and carcinogenic risks of adults and children were seriously higher than the safety level. The non-carcinogenic and carcinogenic risks in the coarse particles were 87.4%-96.2% and 108%-117% of that in fine particles, respectively. These results imply that adults and children were suffered from serious carcinogenic risks above the safety level mainly caused by As that emitted from coal combustion in 4 sites from the SYRD region. Therefore, strict controlling stragtagy should be developed to reduce the levels of toxic elements especially for As that emitted from coal combustion.